The platform economy and transformations in the world of work: The case of delivery platform workers in Santiago, Chile - Antonia Asenjo Cruz; Alberto Coddou Mc Manus; Rishabh Kumar Dhir (International Labour Organization (ILO), 2023)
The growth of digital labour platforms has significantly changed the world of work in Santiago, Chile, especially in the taxi and delivery sectors. This has gained even further prominence since the outbreak of the coronavirus disease (COVID-19) pandemic. Delivery platforms, in particular, have gained prominence offering various services, such as delivery from restaurants, supermarkets and pharmacies, with a promise of higher efficiency. However, this growth has also brought attention to the challenges faced by the workers on these platforms. Debates are ongoing about how to provide fair working conditions for platform workers. Chile has recently taken legislative measures in this direction. This paper aims to contribute to this debate by focusing on the diverse experiences of mobile application-based delivery workers in the country, while also examining the business model of delivery platforms that rely on new technologies to mediate work, as well as the consequences for workers. This paper draws on the data from the in-person survey conducted in Santiago in 2019, involving 259 mobile application-based delivery workers and 50 traditional delivery workers, as well as a follow-up survey conducted during the COVID-19 pandemic in August 2020. The paper provides insights into how different delivery platforms have operated in Chile and their effects on workers in terms of earnings, working hours, occupational health and safety, and social protection. The paper also examines the algorithmic management practices of delivery platforms and their impact on worker flexibility and autonomy. It highlights the precarious and vulnerable situation of these workers, which had been exacerbated by the COVID-19 pandemic. The paper also shows, however, how platform workers have started to organize and demand better working conditions. Lastly, as Chile moves towards implementing a new law to regulate platform work, the paper identifies key challenges that need to be addressed to ensure that all platform workers have access to decent work.
Keywords: 330; Logistikdienstleister; Mobile Anwendung; Arbeitsbedingungen; Soziale Sicherheit; Lohn; Netzwerkökonomik; Santiago (Chile); Chile